Recording thoughts while memorizing music: a case study - Lisboa, Tania; Chaffin, Roger; Demos, Alexander P. (Frontiers in Psychology, 2015)
Musicians generally believe that memory differs from one person to the next. As a result, memorizing strategies that could be useful to almost everyone are not widely taught. We describe how an 18-year old piano student (Grade 7, ABRSM), learned to memorize by recording her thoughts, a technique inspired by studies of how experienced soloists memorize. The student, who had previously ignored suggestions that she play from memory, decided to learn to memorize, selecting Schumann’s “Der Dichter Spricht” for this purpose. Rather than explicitly teaching the student how to memorize, the teacher taught her to record her thoughts while playing by marking them on copies of the score, adapting an approach used previously in research with experienced performers. Over a 6½ week period, the student recorded her thoughts during practice (5 times) and while performing from memory for the teacher (3 times). The student also video-recorded three weeks of practice, three performances, and the reconstruction of the piece from memory after a 9½-weeks break. The thoughts that the student reported were prepared during practice, stable over time, and functioned as memory retrieval cues during reconstruction. This suggests that the student memorized in the same way as the more experienced musicians who have been studied previously and that teaching student musicians to record their thoughts may be an effective way to help them memorize. The speed and durability of her memorization surprised the student, inspiring her to perform in public and to use the same technique for new pieces.